Carbon Dot-Based Nanoparticles: A Promising Therapeutic Approach for Glioblastoma - Wang Y; Wu H; Guo Y; Li F; Zhang H (International Journal of Nanomedicine)
Yongzhi Wang,1,2,* Hao Wu,3,* Yu Guo,4 Fangbao Li,4 Hengzhu Zhang4 1Department of Neurosurgery, Fu Yang People’s Hospital, FuYang, People’s Republic of China; 2Department of Neurosurgery,The Second Affiliated Hospital of Soochow University, Suzhou, People’s Republic of China; 3Department of Neurosurgery, The Second Affiliated Hospital of Xi’an Medical University, Xi’an, People’s Republic of China; 4Department of Neurosurgery, Northern Jiangsu People’s Hospital Affiliated to Yangzhou University, Yangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hengzhu Zhang, Department of Neurosurgery, Northern Jiangsu People’s Hospital Affiliated to Yangzhou University, No. 98 Nantong West Road, Yangzhou City, Jiangsu Province, People’s Republic of China, Email zhanghengzhu@sina.com Yongzhi Wang, Department of Neurosurgery, Fu Yang People’s Hospital, No. 501 Sanqing Road, Yingzhou District, Fuyang City, Anhui Province, People’s Republic of China, Email wangyongzhi.369@163.comAbstract: Glioblastoma (GBM) is a malignant tumor that currently still faces challenges for a complete cure. Although GBM treatment has made great progress, the prognosis of patients is still poor due to interference of various factors in treatment such as the blood-brain barrier (BBB), grade malignancy, intra- and intertumor heterogeneity, drug resistance, and poor targeting of anti-tumor drugs. In recent years, with marked advances in nanotechnology, different types of nanodrug delivery systems have been developed and have been considered as a promising therapeutic measure to gradually overcome chemotherapy resistance and improve tumor targeting. Carbon dots (CDs), as a new type of therapeutic NP, have become a research hotspot of concern for many researchers in recent years. NPs based on CDs have high modifiability and functionalization, allowing for covalent binding with chemotherapy drugs, genes, immune cells and photosensitizers, effectively targeting tumor cells and reducing peripheral cytotoxicity. However, at present, CDs are still in the basic research stage or the preclinical exploratory research stage, and has not yet entered the clinical trial stage or the implementation and application stage. Here, we review the fundamental principles of CDs in the broader field of nanotechnology, their development history, classification, synthesis, and potential for tumor treatment. Especially in the treatment of cancer, CDs can not only participate in photodynamic therapy, photothermal therapy, sonodynamic therapy, chemodynamic therapy, and chemotherapy, but also in multi-modal combination therapy. Here, we hope to provide some insights for further research.Keywords: glioblastoma, cancer treatment, carbon dots, therapeutic approach